Thioredoxin, Glutathione and Related Molecules in Tumors of the Nervous System - Branco, Vasco; Pimentel, José; Brito, Maria A.; Carvalho, Cristina (Current Medicinal Chemistry, 2020)
Background: Central Nervous System (CNS) tumors have a poor survival prognosis due to their invasive and heterogeneous nature, in addition to the resistance to multiple treatments. Objective: In this paper, the main aspects of brain tumor biology and pathogenesis are reviewed both for primary tumors of the brain, (i.e., gliomas) and for metastasis from other malignant tumors, namely lung cancer, breast cancer and malignant melanoma which account for a high percentage of overall malignant brain tumors. We review the role of antioxidant systems, namely the thioredoxin and glutathione systems, in the genesis and/or progression of brain tumors. Methods: Although overexpression of Thioredoxin Reductase (TrxR) and Thioredoxin (Trx) is often linked to increased malignancy rate of brain tumors, and higher expression of Glutathione (GSH) and Glutathione S-Transferases (GST) are associated to resistance to therapy, several knowledge gaps still exist regarding for example, the role of Peroxiredoxins (Prx), and Glutaredoxins (Grx). Conclusion: Due to their central role in redox homeostasis and ROS scavenging, redox systems are potential targets for new antitumorals and examples of innovative therapeutics aiming at improving success rates in brain tumor treatment are discussed.
Keywords: Brain tumors